Who Ministers to Whom: Matthew 25:31–46 and Prison Ministry. (3rd June 2013) - Vargas, Alicia
Abstract This essay sees Matthew 25:31–46 as Jesus' offer of both gift and challenge: disciples will simultaneously minister to and be ministered to by Jesus in jail and prison. Following a consideration of two different dominant ways of interpreting the passage in the literature—what are sometimes called the missionary and the social justice interpretations—and Luther's reading of the passage as falling under the Fifth Commandment, the essay invites the reader to engage the transformative consequences of "seeing" Jesus imprisoned in the U.S. criminal "justice" system.